ESG Investment and SME Green Policies - Naoyuki Yoshino; Aashi Agarwal; KE Seetha Ram (Asian Development Bank Institute (ADBI), 2024)
This paper examines the current landscape of environmental, social, and governance (ESG) investing by focusing on environment. We analyze the discrepancies in ESG scoring methodologies among different rating agencies and demonstrate how these inconsistencies can lead to distorted investment decisions. To address this issue, we propose a unified approach based on a net carbon tax, which incorporates both carbon emissions and companies' green efforts. We address how carbon trading, carbon pricing and green bonds differ across various countries. This can lead to distortions in production location because global companies relocate their production units based on tax rates and various fees. We also explore the potential alignment of carbon tax, green bonds, and carbon pricing mechanisms. We argue that by standardizing the measurement of greenhouse gas emissions, these instruments could converge to provide consistent signals for investors and policymakers. The burdens and consequences of each policy will differ, which will cause the relocation of global companies based on weaker regulation on environments. We also discuss the importance of including small and medium-sized enterprises (SMEs) in emissions reduction efforts and the potential implications of central banks purchasing green bonds. We have also offered key messages for policymakers in Asian countries.
Keywords: Q56; G11; H23; F18; Q58; 330; environmental; social; and governance (ESG); small and medium-sized enterprises (SMEs); green policies; net carbon tax